Sources of stress and its relationship to self-regulation Special Education Teachers (Shadow Teacher) In kindergartens and primary schools - محمد, آ. م. د. نزيرة صالح; محمد, پەروەر احمد (Sulaimani Journal for Humanities, 2025)
This study aimed to identify sources of psychological stress and their relationship to self-regulation among special education teachers (shadow) in kindergarten and primary schools, and to identify the level of sources of psychological stress and self-regulation among special education teachers. Also, it aims at analyzing the statistical difference in the sources of psychological stress and their relationship to self-regulation among special education teachers (shadow). Due to demographic variables that include the kind of study, age, work experience, and in order to achieve the objectives of this approach was adopted. The research tool consisted of two scales: a psychological stress resources scale adapted from a master's thesis (Qader, 3202) and consisting of 35 items, and a self-regulation scale adapted from a study (Al-Kafawin, 2021) and consisting of 28 items. The study concluded that there is an inverse relationship between psychological stress and self-regulation among private school teachers in Sulaymaniyah kindergartens and Chamchamal schools. Psychological stress among special education teachers in kindergartens in Sulaymaniyah Governorate is high, while the level of self-regulation is low. Psychological stress and self-regulation among special education teachers in Chamchamal District are high. There are no statistically documented differences in psychological stress among kindergarten and basic school teachers according to age, economic status, and years of service. There are also no statistically significant differences in self-regulation according to economic status and years of service. In contrast, there is a difference in self-regulation depending on age. Based on these findings, the researchers presented several recommendations and suggestions.
Keywords: psychological stress; self regulation; shadow teachers; kindergarten; primary school